Fungsi Bahasa Ibu dalam Kegiatan Pembelajaran Siswa Kelas 1 (Satu) di SD. Negeri Bilese Desa Hueknutu, Kecamatan Takari, Kabupaten Kupang: Indonesia - Kolnel, Arnol; Mesah, Jeff Wilfred (Universitas Persatuan Guru 1945 NTT, 2023)
Language is a communication tool for humans, this shows that the smoothness of a communication depends on the mastery of a language. A child in his communication development will use the language used in his family environment and that is the first language of the child and becomes the mother tongue for the child. This study aims to determine the function of mother tongue in learning grade 1 students at SD Negeri Bilese,Desa Hueknutu, KecamatanTakarti Kabupaten Kupang . The theory used is Psycholinguistic theory. The results showed that the function of mother tongue in learning activities for first grade students at SD Negeri Bilese, Huekntutu Village, Takari sub-district, Kupang Regency consisted of social functions and referential functions.